Evaluation of the Anti-Histoplasma capsulatum Activity of Indole and Nitrofuran Derivatives and Their Pharmacological Safety in Three-Dimensional Cell Cultures - Vaso, Carolina Orlando [UNESP]; Bila, Níura Madalena [UNESP]; Pandolfi, Fabiana; De Vita, Daniela; Bortolami, Martina; Bonatti, Jean Lucas Carvalho [UNESP]; de Moraes Silva, Rosângela Aparecida [UNESP]; Gonçalves, Larissa Naiara Carvalho [UNESP]; Tudino, Valeria; Costi, Roberta; Di Santo, Roberto; Mendes-Giannini, Maria José Soares [UNESP]; et al. (My University, 2022)
Histoplasma capsulatum is a fungus that causes histoplasmosis. The increased evolution of microbial resistance and the adverse effects of current antifungals help new drugs to emerge. In this work, fifty-four nitrofurans and indoles were tested against the H. capsulatum EH-315 strain. Compounds with a minimum inhibitory concentration (MIC90 ) equal to or lower than 7.81 µg/mL were selected to evaluate their MIC90 on ATCC G217-B strain and their minimum fungicide concentration (MFC) on both strains. The quantification of membrane ergosterol, cell wall integrity, the production of reactive oxygen species, and the induction of death by necrosis–apoptosis was performed to investigate the mechanism of action of compounds 7, 11, and 32. These compounds could reduce the extracted sterol and induce necrotic cell death, similarly to itraconazole. Moreover, 7 and 11 damaged the cell wall, causing flaws in the contour (11), or changing the size and shape of the fungal cell wall (7). Furthermore, 7 and 32 induced reactive oxygen species (ROS) formation higher than 11 and control. Finally, the cytotoxicity was measured in two models of cell culture, i.e., monolayers (cells are flat) and a three-dimensional (3D) model, where they present a spheroidal conformation. Cytotoxicity assays in the 3D model showed a lower toxicity in the compounds than those performed on cell monolayers. Overall, these results suggest that derivatives of nitrofurans and indoles are promising compounds for the treatment of histoplasmosis.
Keywords: antifungal activity; cytotoxicity; drug repositioning; Histoplasma capsulatum; indoles; mechanisms of action; nitrofurans; pharmacological replacement; spheroids; three-dimensional models